2020
DOI: 10.1093/cid/ciaa1202
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and safety study of co-administration of albendazole, diethylcarbamazine, Ivermectin and azithromycin for the integrated treatment of Neglected Tropical Diseases

Abstract: Background Pharmacokinetic data are a pre-requisite to integrated implementation of large-scale mass drug administration (MDA) for neglected tropical diseases (NTDs). We investigated the safety and drug interactions of a combination of azithromycin (AZI) targeting yaws and trachoma, with the newly approved ivermectin, albendazole, diethylcarbamazine (IDA) regime for Lymphatic Filariasis. Methodology An open-label, randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our findings have important implications for countries that are considering the use of the triple-drug regimen for elimination of lymphatic filariasis. The consistently high efficacy of the triple-drug regimen seen in this study and in other areas of Papua New Guinea 8 , 26 suggests that elimination of lymphatic filariasis is a feasible goal for this country, which has the highest burden of lymphatic filariasis in the South Pacific. 27 Coverage and compliance are key for any mass drug administration programme, and the superior treatment regimen will not fix poor compliance.…”
Section: Discussionsupporting
confidence: 49%
“…Our findings have important implications for countries that are considering the use of the triple-drug regimen for elimination of lymphatic filariasis. The consistently high efficacy of the triple-drug regimen seen in this study and in other areas of Papua New Guinea 8 , 26 suggests that elimination of lymphatic filariasis is a feasible goal for this country, which has the highest burden of lymphatic filariasis in the South Pacific. 27 Coverage and compliance are key for any mass drug administration programme, and the superior treatment regimen will not fix poor compliance.…”
Section: Discussionsupporting
confidence: 49%
“…The AZI used was generic AZI (500 mg tablet) produced by Kern Pharmaceuticals for the study. Volunteers were instructed to fast overnight and were given by direct observation AZI 30 mg/kg (maximum 2 g/dose) in three treatment regimens (John et al, 2020). Serial blood samples were collected at baseline, 1, 2, 3, 4, 6, 8, 12, 24, 48 and 72 h following the dose.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported the results of a clinical study that compared the pharmacokinetics of administration of IDA separately (lymphatic filariasis regimen) or AZI separately (yaws regimen) with coadministration of IDA and AZI (combined treatment regimen). Compared to separately administered treatment, the study demonstrated an absence of clinically relevant drug-drug interactions, and no severe adverse events (AE) were observed [12] . These findings paved the way for more extensive field studies to evaluate the safety of integrated MDA.…”
Section: Introductionmentioning
confidence: 92%